MEMBANGUN IMAJINASI KEHIDUPAN SOSIAL MELALUI PERANCANGAN KARAKTER PENDUKUNG PROFIL MASKOT KAMPUS FSRD UNTAR - Darmo, Budi; Chandra, Edy (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
Mascots in their development have become a visual identity tool for a company, for designers must know the main factors needed by users to recognize mascots (Lin et al., 1999). The form of a mascot is generally in the form of representatives in the form of animals and the like. Campus is an educational institution that is equivalent to companies that need mascot figures to build their image. Mascots are fictional figures who are able to build identity in creating and expressing the personality of the brand they represent (Ardi &; Munawarah, 2021). FSRD Untar as an educational institution that seeks to build its visual character through mascot figures in human form which are generally the hallmark of mascots of a company (Chandra, 2022). The form of the mascot designed by FSRD is only limited to the appearance of its visual profile, not yet to an interesting and more complex